Crypto Asset as a Transaction Tool in the Perspective of Economic Analysis of Law: Legal Consequences and Ius Constituendum: Aset Kripto sebagai Alat Transaksi dalam Perspektif Analisis Hukum Ekonomi: Konsekuensi Hukum dan Ius Constituendum - Ningsih, Dita Damayanti Sasmito; Achmad, Dimas Hikari; Dewi, Elreddian Kusuma; Purnami, Yessy Arinta Puji (Universitas Muhammadiyah Sidoarjo, 2022)
This normative legal research examines the economic and legal aspects of using crypto assets as a means of business transactions in Indonesia. The study uses a concept and legislation approach to analyze the legal consequences of crypto assets as transaction tools in digital business transactions. The research finds that crypto assets can be traded as goods in accordance with existing regulations, but cannot be used as legal tender in digital business transactions. Any digital transaction that uses only crypto assets as currency is null and void, and subject to criminal sanctions. To regulate the use of crypto assets as transaction tools, the study suggests breaking down the substance of Bappebti Regulation into two characters, regeling and beshikking. The implication of this research is that further studies and proposals are needed from Bappebti to determine whether crypto assets can be used as currency in the future, and to ensure that future regulation aligns with the principles of Economic Analysis of Law. Highlights: Crypto assets can be traded as goods in accordance with regulations. Crypto assets cannot be used as legal tender in digital business transactions. Regulation of crypto assets as a transaction tool needs to be further developed and clarified.